Malignant stromal tumor of the stomach with giant cystic liver metastases prior to treatment with imatinib mesylate - Čolović Radoje (Vojnosanitetski Pregled, 2013)
Introduction. Gastrointestinal stromal tumors (GISTs) are rare and account for 0.1%-3% of all gastrointestinal neoplasms. GISTs are most commonly located in the stomach (60%) and 20%-25% are malignant, with metastases involving the peritoneum or the liver. Cystic liver metastases are extremely rare. Only two previous cases of patients with cystic liver metastases, prior to treatment with imatinib mesylate, have been described so far. Case report. We reported a 52-year-old woman presented with a history of abdominal fullness and discomfort. Clinical examination revealed two palpable masses, first in the right upper abdomen and second left to the umbilicus. Examinations revealed 4 cystic metastases in the liver, 3 in the right lobe (including a huge one measuring 20.5 x 16 cm), and 1 in the left lobe, together with a primary tumor on the greater curvature of the stomach. Gastric tumor was removed with a Billroth II gastrectomy. Partial excision of the largest liver metastasis was performed for histopathology. Immunohistochemistry confirmed the diagnosis of a GIST in both tissue samples. After an uneventful recovery the patient was commenced on imatinib mesylate therapy. The patient remainsed symptom-free at 24 months follow-up. Conclusion. This was the third reported case of gastric GIST with giant cystic liver metastases present prior to treatment with imatinib mesylate. Although extremely rare, GISTs may present with cystic liver metastases prior to treatment with imatinib mesylate, and should be considered in the differential diagnoses of patients with liver cysts of uncertain aetiology.